“Those who eat coca are sorcerers”: Demonology and Coca in the Works of Guaman Poma de Ayala - Salazar-Calvo, Giovanni (2020)
In this essay I argue that Guaman Poma de Ayala strategically used demonology-related discourses to negatively represent the consumption of coca in the Andean world. Said this, the native chronicler also claimed that the use of this plant did not hinder the orderly development of the viceroyalty. I propose that Guaman Poma’s strategy intends to confrm that coca did not prevent the Incas to govern the viceroyalty of Peru along with the Spaniards. By means of demonology-related discourses, the author most likely gained the sympathy of his Christian readers. At the same time, however, he started a way to look at Inca society andits use and consumption of coca in a positive light when talking about economic and civil matters. This strategy allowed him to defend the idea that the incas were able to use political power along with the Spaniards without any conﬂict with European theological principles.